1985
DOI: 10.1007/bf01351350
|View full text |Cite
|
Sign up to set email alerts
|

Single unit activity in the peripheral lateral line system of the cichlid fishSarotherodon niloticus L.

Abstract: The activities of single afferent fibers were recorded in the trunk lateral line nerve of the cichlid fish Sarotherodon niloticus L. Using both electrophysiological recordings and neuroanatomical tracing techniques, the number, arrangement, and innervation of superficial (SNs) and canal (CNs) neuromasts were determined. Both, SNs and CNs, are innervated by several afferent fibers of different diameters and efferent fibers. The CNs and SNs are neuronally separated: afferent fibers which innervate both CNs and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(43 citation statements)
references
References 48 publications
6
36
1
Order By: Relevance
“…These preliminary experiments confirmed that the neural responses are linear relative to stimulus amplitude, as found in other lateral line systems (e.g. Kroese et al, 1978;Münz, 1985;see Results below).…”
Section: Methodssupporting
confidence: 83%
“…These preliminary experiments confirmed that the neural responses are linear relative to stimulus amplitude, as found in other lateral line systems (e.g. Kroese et al, 1978;Münz, 1985;see Results below).…”
Section: Methodssupporting
confidence: 83%
“…Although silent fibres that previously have been isolated in the toadfish lateral line were not isolated here (Palmer et al, 2005), several fibres of relatively low frequency were characterised and found to have phasic properties. These types of fibres have also been reported in a closely related toadfish, the midshipman (Weeg and Bass, 2002), and in other teleosts (Coombs and Janssen, 1990;Kroese and Schellart, 1992;Montgomery et al, 1988;Munz, 1985;Wubbels et al, 1990).…”
Section: Spontaneous Activitysupporting
confidence: 67%
“…Each neuromast on the surface is not innervated individually, but a group of 5 to 10 are innervated jointly [14,59]. This implies that the flow velocity information is effectively averaged over a small region on the fish surface before any further processing.…”
Section: Superficial Subsystemmentioning
confidence: 99%
“…In contrast to the superficial neuromasts, each individual canal neuromast is independently innervated [59]. This emphasis on the importance of each individual canal neuromast is also evident in the shape of the canals, which are frequently irregularly shaped in order to magnify the fluid velocity at the location of the neuromasts [28] (see lower left cephalic canal system in Figure 2-2 for example).…”
Section: Canal Subsystemmentioning
confidence: 99%